Boosting Sales Turnover of Sumber Podang Honey with Digital Campaign - Nabela, Yuhana Della; Muslih, Basthoumi (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This study aims to analyze the effectiveness of digital campaigns in increasing sales turnover in MSMEs Sumber Podang Honey. Design/Methode/Approach: This study uses a qualitative approach with in-depth interviews and participatory observation as a data collection method. The informants involved are consumers and owners at MSMEs Honey Sumber Podang. Research Finding: The results of the study show that using the 5R sales strategy and through the digital sales strategy campaign can be used as an effective strategy in increasing sales turnover in MSMEs Honey source podang and also expanding the reach of sales promotion. Theoretical contribution/Originality: This study provides new insights into the importance of sales strategy in the context of sales promotion through digital campaigns, especially in terms of efforts to increase sales turnover. These findings add to the literature on managing online sales strategies Implication: This study recommends the application of digital sales strategy campaigns in small and medium-sized companies to increase sales results. Research limitations: The limitations of this study are the focus on one location and the lack of generalization of results. Further research is suggested to cover more locations and industry variations.